Photocatalytic Degradation of Different Dyes Using TiO2 with High Surface Area: A Kinetic Study (Journal of Scientific Research, 2013)
Nanocrystalline TiO2 was synthesized by using one step sol-gel method and characterized by SEM, XRD and EDS. UV-Vis spectroscopic technique has been used for studying the photocatalytic degradation kinetics of methylene blue (MB) and congo red (CR). A comparative study with commercial TiO2 (P25) was also done to find out the effectiveness of this synthesized TiO2. The synthesized TiO2 exhibited a high photocatalytic activity for the degradation of MB and CR but the commercial TiO2 was more efficient.Keywords:  Nanocrystalline TiO2; Methylene Blue; Congo Red; Photocatalytic degradation kinetics.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.11641 J. Sci. Res. 5 (2), xxx-xxx (2013)